Incorporating sustainable development objectives into development plans through strategic environmental assessment - Abdullah, Muhammad Faris; Ariffin, Ishak (Malaysian Institute of Planners, 2003)

(untitled)
Efforts aimed at delivering sustainable development and promoting nature conservation in the planning and decision-making system in Malaysia has begun since the late 1970s. The growing importance of the preservation and protection of the environment against degradation have been highlighted in the Five Year Plans from 1980s. Over the same period, a series of strategies for sustainability, entitled Conservation Strategies, was also being prepared in Malaysia, culminating in a National Conservation Strategy (NCS) in 1993. These strategies for sustainability were aimed at providing the framework for sustainable development. The general consensus is that prevention is better than remedial action. Potential impacts must be addressed at the planning stage before development decisions are made.